Chapter Gregorio XI e la rinascita di San Miniato al Monte. Un esempio di riforma monastica promossa nel Trecento dai monaci di Monte Oliveto - Tagliabue, Mauro (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
The monastery of San Miniato, formerly Black Benedictine, in 1373 was entrusted to the care of the Monte Oliveto's monks with the favor of pope Gregory XI. The paper retraces the reasons of this passage of observance, which took place during a difficult period for the city of Florence, engaged in the War of the Eight Saints, and in the context of an almost generalized crisis of Benedictine abbeys, analyzing the resumption of regular life and institutional innovations, such as the temporary mandate of abbots; until the site was abandoned after the mid-sixteenth century.